Desempenho de Eriopis connexa (Germar) (Coleoptera: Coccinellidae) resistente à Lambda-cialotrina - Ferreira, Emerson dos Santos (2012)
Fitness of insecticide resistant insect populations can be different to susceptible insect populations regarding adaptive costs. Therefore, this study investigated the fitness of Eriopis connexa (Germar) (Coleoptera: Coccnellidae) population resistant to lambda-cyhalothrin, as well as its predation rate on Aphis gossypi (Glover) (Hemiptera: Aphididae). The insects used to run the bioassays were reared under laboratory conditions of 25 ± 1oC and 12:12h (L:D) photoperiod and fed with Anagasta kuehniella (Zeller) (Lepidoptera: Pyralidae) eggs. The field resistant population of E. connexa (RR) was maintained under selection pressure at each adult generation in the laboratory by exposing them to the LD50-dose (0.25 mg a.i./mL of lambda-cyhalothrin at technical grade) determined after 12 successive generations of selections in the laboratory. The susceptible population (SS) was reared at the same condition; however, without exposing the insects to the insecticide. Non-treated RR females and treated recovered females (RRr) after lambda-cyhalothrin topic treatment with 0.05, 0.10 and 0.25 mg a.i./mL produced on average 50% less eggs than SS females. All other adult life history characteristics were similar among SS, RR and RRr populations. Among the developmental characteristics for offspring produced by SS, RR, and RRr females was observed lower larval viability and weight of adult males for RRr offspring. Furthermore, females from SS, RR and RRr populations exposed to prey shortage between 3rd- and 13th-day in the adult stage exhibited statistically similar survival ranging from 48 to 63 days. However, egg production was significantly higher for females SS (average = 290 eggs), followed by females RR (180 eggs), and RRr (50 eggs) during this period. The average consumption of cotton aphid during five consecutive days was significantly higher for ladybeetles SS, followed by RR and RRr up to the third day of observation. However, after the fourth day, there was no difference in the aphid consumption among the three populations SS, RR, and RRr. The results show that females RR have lower reproductive output in comparison to females SS, and it is not related to the knockdown effect; however, the costs of recovering from knockdown interferes with egg production under food shortage, with larval viability and adults predation rate. Thus, we can conclude that E. connexa population resistant to the lambda-cyhalothrin exhibits adaptive costs which is increased when subjected to prey shortage.